Development of a novel target-enriched multiplex PCR (Tem-PCR) assay for simultaneous detection of five foodborne pathogens. (June 2016) - Xu, Yi-Gang; Liu, Zhong-Mei; Zhang, Bai-Qi; Qu, Min; Mo, Chun-Sheng; Luo, Jia; Li, Su-Long
Abstract: In the present study, a novel target-enriched multiplex PCR (Tem-PCR) assay was developed for simultaneous detection of Salmonella spp., Listeria ( L .) monocytogenes, Staphylococcus ( S .) aureus, Escherichia ( E .) coli O157:H7 and Shigella spp.. DNA primers including universal primer and composite primer pairs were used in this Tem-PCR assay. Of which, the universal primer was linked to the 5'-end of each specific primer designed targeting Salmonella invA gene, Staphylococcus aureus femA gene, Shigella ipaH gene, Listeria monocytogenes hly gene and Escherichia coli O157:H7 rfbE gene, respectively, generating the composite primers. During PCR amplification, the composite primer pairs were employed to enrich target genes of different pathogens in initial cycles and the universal primer was employed to enrich the amplicons produced with the composite primers priming in later PCR cycles. Significantly, the Tem-PCR assay overcomes the amplification disparity resulting from primers competition observed in conventional multiplex PCR assay. With the evaluation of the Tem-PCR assay for the detection of these five foodborne pathogens, the assay showed high specificity to the target bacteria with an analytical detection limit of <2.0 × 10 2 CFU/mL for each, and practical detection capability, suggesting a novel multiplex PCR method for detecting foodborne pathogens. Highlights: A novel Tem-PCR assay for detection of five foodborne pathogens was developed. The assay overcomes the amplification disparity resulting from different primers. The assay has been validated in naturally contaminated foods. The assay is helpful for developing high-throughput multiplex PCR assay.